Operational Managing Analysis in Driving Product Marketing to a Global Scale (Case Study PT Indofood CBP) - Suhairi Suhairi; Habib Lauda Nararya; Silvi Tri Wardani; Tria Wardani; Indah Mutiara Ayu (Jurma : Jurnal Program Mahasiswa Kreatif, 2023)
The operational activities of the company have a major urgency in management to the level of production carried out. The operational system as well as the right management can affect the long-term sustainability of the company. In a global market share, it is necessary to have the role of operational management to improve marketing patterns as well as the expected gains. This process is seen in terms of planning, organizing, implementing up to the monitoring stage. This study aims to analyze the operational managing program used to encourage the marketing activities of a product to reach a global scale by PT Indofood CBP. The research method used is a qualitative research method using a descriptive type approach. The main data source used is information that supports the structure or operational husk of PT Indofood CBP itself and is supported by secondary data sources in the form of literature relevant to the research topic. The collection technique used was a literature study. The research results show that.